Educação e Filosofia em Rousseau na perspectiva teatral - PEREIRA, Elayne de Araujo (2023)
The purpose of this work is to articulate an interdisciplinary relationship between Education, Theater and Philosophy from the thought of Jean-Jacques Rousseau, specifically based on the worksDiscourse on the Sciences and the Arts, Emílio or On Education, It isLetter d'Alembert on the spectacles, the latter written as a response to the publication of the entryGeneva,no volume VII yesEncyclopedia. Rousseau, contrary to the quarrel between the philosophes who defended the pedagogical project of the theater, the refinement of virtues and customs, uses the study of the human condition to show how much the spectacles of progress lead to the corruption of men in society. In this way, the philosopher exposes that the theater does not have the power to instruct, as the illuminist d'Alembert illustrated in his entry, when he outlined that the laws on comedy companies in Geneva should be revoked for the education of young people and citizens, like the Greeks of Athens. Thus, at first, the education of men about the arts is investigated, based on morals and politics since the Greeks, as well as the position of the philosopher Plato when he expelled the poets from the city in his Republic. This behavior is very similar to Rousseau's position in modernity with the "progress" of man in society. After that, it identifies the criticism regarding the installation project of the shows in the improvement of taste and customs, considering the quarrel of the philosophers of illustration: Voltaire, Diderot and d'Alembert to Rousseau's denial about theatrical poetics in the Republic of Geneva. Then, the objective is to understand Emílio's natural education in face of the proposal of the party as a way for the civility of modern men. Finally, the understanding of Rousseau's designs in relation to theater and education generated since the ancients is concluded. These designs aimed at updating the Greek Paidéia in modernity through parties, so that men would not be corrupted by the depravity of society through a civic spectacle, in which there is the extermination of representation. At the party, everyone is equal, without the need for mediations, deserving the same amount of light.